ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN MELALUI RASIO SOLVABILITAS PADA PT. INDORITEL MAKMUR INTERNASIONAL TBK (INDOMARET) TAHUN 2019 – 2023 - Anggraeni, Devi; Angraini, Selvi; Nurhaliza, Reza; Putri Biloro, Berlin Anggraeni; Rowesha Citra, Cindy (Universitas Muhammadiyah Metro, 2025)
Financial statement analysis is an essential tool for comprehensively assessing a company's financial performance. This study aims to evaluate the financial performance of PT Indoritel Makmur Internasional Tbk (Indomaret) through solvency ratios during the period from 2019 to 2023. By utilizing ratios such as Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), this research reveals the company's financial stability and its ability to meet long-term obligations. The results of the analysis indicate that despite fluctuations, the company's financial structure remains healthy with efficient debt management. This study recommends that the company exercise caution in financing decisions to maintain financial stability in the future.